Operator Splitting Schemes for the Non-Stationary Thermal Convection Problems (Journal of Computational Mathematics, 2018)
In this work, a new numerical scheme is proposed for thermal/isothermal incompressible viscous flows based on operator splitting. Unique solvability and stability analysis are presented. Some numerical results are given, which show that the proposed scheme is highly efficient for the thermal/isothermal incompressible viscous flows.
Keywords: $θ$ scheme; Stability; Isothermal incompressible viscous flows.